Mangrove restoration without planting - Kamali, B.; Hashim, Roslan (2011)
Mangrove forests are disappearing at an alarming rate. Mangrove planting is the most common method of restoring these forests. However, this approach is not often successful, especially when the reasons for mangrove degradation were not removed prior to planting new seedlings or propagules. A successful mangrove restoration project may not necessarily include a planting phase. When the stressors are removed and suitable environmental conditions such as correct hydrology and calm area, particularly on exposed coasts, are provided, natural regeneration processes could recover mangroves from degradation. This paper describes an approach to mangrove restoration applied to an exposed shoreline on the west coast of Peninsular Malaysia. In this method a detached breakwater was erected seaward at the shoreline to shelter the restoration area from wave action, prevent the ongoing erosion and promote sediment deposition raising the elevation of the substrate to the target elevation. Survival of Avicennia marina seedlings transplanted in the sheltered area was significantly affected by sediment burial (P< 0.05). However, about eight months after construction of the breakwater, the sedimentation rate decreased and the substrate became stable. Subsequently, natural recruits appeared on the site. We postulate that waterborne seeds or propagules were available from adjacent stands in the study area but wave exposure reduced the possibility of natural recruitment. Thus the breakwater presence provided favourable conditions which could attract mangrove recruits, facilitating reestablishment and natural recovery of the mangrove ecosystem without planting.